Competence framework of information technology for students of Thai Nguyen University of Agriculture and Forestry - Hua Thi Toan; Trinh Thanh Hai; Do Trung Kien (Institute of Advanced Engineering and Science, 2023)
Currently, with the positive impact of information technology (IT), the world’s agriculture is gradually shifting from the traditional agricultural model to the digital agricultural model, creating high productivity, increasing the product value and labor productivity. However, the agriculture with applied digital also requires laborers to be capable of applying IT in the agricultural sector. On the basis of theoretical research, output standards from bachelor training programs in the field of agriculture in the world and Vietnam, along with practical investigation results, the article focuses on two main contents: clarify the content of IT application capacity of a student in the field of agriculture and forestry; building a competence framework and assessment criteria for IT application competence for students in the field of agriculture and forestry. The results of the article are documents for Thai Nguyen University of Agriculture and Forestry as well as training institutions for bachelors and engineers in agriculture and forestry to refer to in the process of developing training programs, assessing outcomes for students, as well as innovating training methods towards developing learners’ capacity.